Editorial Matter - Yinyang: Jurnal Studi Islam Gender dan Anak (Yinyang: Jurnal Studi Islam Gender dan Anak, 2021)
this section for upload any editorial material, such as front cover, back cover, eratum, corigendum, and retraction.